Management of retrorectal supralevator abscess: results of a large cohort - Téoule, Patrick; Seyfried, Steffen; Joos, Andreas; Bussen, Dieter G.; Herold, Alexander (International journal of colorectal disease, 2018)
PurposeProximal intersphincteric fistulas with proximal extension causing supralevatoric, retrorectal abscesses are a rare disease. There is only very limited experience, with small groups, and the limited published literature confirms the complexity of diagnostics and treatment. The aim of this study was to evaluate transrectal internal abscess drainage as planned definitive treatment.MethodsWe retrospectively studied medical records of all patients with the diagnosis of retrorectal abscesses that underwent transrectal internal abscess drainage in the Department of Colo-proctology of the University Medical Centre Mannheim (2003-2012).ResultsOne hundred nine patients were operated on retrorectal abscesses, 70 (64.2%) men and 39 (35.8%) women. Mean age was 45.3 years (18-81). In 96 cases (88.1%), only a transrectal internal abscess drainage was performed as planned definitive treatment. Primary healing occurred in 60 patients (62.5%). A second transrectal internal drainage procedure was necessary in 27 cases (28.1%) to assure complete internal drainage. All secondary procedures led to subsequent healing. A combined surgical treatment due to coexisting fistula tracts to the perianal skin or additional ischioanal abscesses was required in 13 patients (11.9%), and an additional seton placement was performed. Nine patients (9.4%) underwent one or more reoperations due to previously unidentified complex coexisting fistulas. Most of these patients were immunosuppressed due to Crohn’s disease. Internal drainage alone was successful in 90.6% with an overall healing rate of 94.5% for the entire population of complex fistulas.ConclusionsTransrectal internal abscess drainage is a safe and highly successful procedure for treatment of retrorectal abscess, with very low risk of postoperative fecal incontinence. Inflammatory bowel disease and immunosuppressives have a negative impact on the healing process.
Gesehen am 13.05.2019